Cooperative learning strategy type STAD for economic business in SMK Bhakti Bangsa - Muhammad Fasya Fanshary Aksa; Maya Gita Cahyani; Amanda Tri Damayanti (Curricula: Journal of Curriculum Development, 2023)
This research aims to evaluate the effectiveness of implementing Student Team Achievement Division (STAD) type cooperative learning strategies in increasing students' interest in learning in Business Economics subjects at BPI Bandung Vocational High Schools (SMK). Evaluation will include comparing student learning outcomes before and after implementing the STAD method, an analysis of student involvement in the cooperative learning process, and student responses to this learning method. Additionally, the research will highlight changes in interactions between students, their confidence in understanding the material, and whether implementing STAD can stimulate active participation in class discussions. The research uses a qualitative approach to explore the influence of the STAD strategy on students' interest in learning with observation and interviews related to implementing the STAD strategy. This qualitative analysis identifies patterns and findings that strengthen the effectiveness of the STAD strategy in increasing student interest and motivation to learn at SMK Bhakti Bangsa Bandung, especially in Business Economics subjects.   Abstrak Penelitian ini bertujuan untuk mengevaluasi efektivitas penerapan strategi pembelajaran kooperatif tipe Student Team Achievement Division (STAD) dalam meningkatkan minat belajar siswa pada mata pelajaran ekonomi bisnis di Sekolah Menengah Kejuruan (SMK) BPI Bandung. Evaluasi akan mencakup perbandingan antara hasil belajar siswa sebelum dan sesudah penerapan metode STAD, analisis tingkat keterlibatan siswa dalam proses pembelajaran kooperatif, serta tanggapan siswa terhadap metode pembelajaran ini. Selain itu, penelitian akan menyoroti perubahan dalam interaksi antar siswa, kepercayaan diri mereka dalam memahami materi, dan apakah penerapan STAD dapat merangsang partisipasi aktif dalam diskusi kelas. Penelitian menggunakan pendekatan kualitatif untuk mendalami pengaruh strategi STAD terhadap minat belajar siswa dengan observasi partisipasi dan wawancara terkait implementasi strategi STAD. Analisis kualitatif ini mengidentifikasi pola-pola dan temuan yang memperkuat efektivitas strategi STAD dalam meningkatkan minat dan motivasi belajar siswa di SMK Bhakti Bangsa Bandung khususnya pada mata pelajaran Ekonomi Bisnis. Kata Kunci: Pembelajaran kooperatif; strategi belajar; STAD; student team achievement division